Aktivitas Antibakteri Ekstrak Etanol Buah Sawo Manila (Manilkara zapota) Muda Terhadap Salmonella typhimurium Berdasarkan Variasi Metode Ekstraksi - Maulita Cut Nuria; Helmi Uci Rachmadhany (Jurnal Inovasi Teknik Kimia, 2026)
Manila sapodilla unripe fruit extracts contain terpenoids, flavonoids, and tannins. The compound's retraction can be influenced by the extraction method, whether hot or cold. The chemical compound content of the extract plays a role in its biological activity, such as antibacterial activity. Salmonella typhimurium bacteria can cause problems in the digestive tract, causing typhoid fever (typhoid). The aim of this study was to determine the antibacterial activity of the ethanol extract of unripe Manila sapodilla fruit against Salmonella typhimurium using several extraction methods. Manila sapodilla unripe fruit simplicia powder was extracted using four methods: maceration, percolation, Soxhlet, and reflux, with 70% ethanol as the solvent. The concentration series of the tested extracts was 20%, 25%, 30%, and 35%. As a negative control, Dimethyl Sulfoxide (DMSO) solvent was used, and a positive control was chloramphenicol at 30 µg/disk. Antibacterial activity test using the disc diffusion method. The observed parameters, namely the zone of inhibition, were analyzed statistically using Friedman's test at the 95% confidence level. The results showed that the ethanol extract of unripe manila sapodilla fruit from several extraction methods produced zones of inhibition: maceration ranged from 6.15-7.30 mm, percolation ranged from 6.46-8.18 mm, Soxhlet ranged from 6.03-8.50 mm, and reflux ranged from 7.26-8.27 mm. Statistical results showed a significant difference in zone of inhibition values from ethanol extracts of unripe manila sapodilla fruit across all extraction methods against Salmonella typhimurium. The reflux method yields the best zone-of-inhibition results because heat makes the compound easier to extract and prevents solvent saturation.